2006
DOI: 10.4049/jimmunol.177.7.4503
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for Viral-Defective Interfering Particles in Enhancing Dendritic Cell Maturation

Abstract: Dendritic cell (DC) maturation is a crucial event in the development of adaptive immune responses that confer long-lasting protection against reinfection with the same virus. Sendai virus strain Cantell has a particularly strong ability to mature DCs independently of type I IFNs and TLR signaling, currently the best-described pathways for the induction of DC maturation. In this study, we demonstrate that defective-interfering (DI) particles present in Sendai virus-Cantell stocks are required for its robust DC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
155
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(169 citation statements)
references
References 48 publications
13
155
1
Order By: Relevance
“…We have previously demonstrated that, differently from most wild-type SeV strains, DCs are capable of detecting SeV strain Cantell (SeV-C) and robustly produce cytokines even in the presence of functioning immune antagonists (20). The DC response to SeV-C requires the presence of defective interfering (DI) particles, known to enhance the induction of type I IFN in infections with many different viruses (21)(22)(23)(24).…”
Section: Endritic Cell (Dc)mentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously demonstrated that, differently from most wild-type SeV strains, DCs are capable of detecting SeV strain Cantell (SeV-C) and robustly produce cytokines even in the presence of functioning immune antagonists (20). The DC response to SeV-C requires the presence of defective interfering (DI) particles, known to enhance the induction of type I IFN in infections with many different viruses (21)(22)(23)(24).…”
Section: Endritic Cell (Dc)mentioning
confidence: 99%
“…Sequences for mouse and human primers used in this study are shown in Table I. Primers used for detection of SeV NP mRNA were previously published (20). For analysis, fold inductions were calculated over mock-infected values and representations of copy number are based on an empirical estimate of 2500 for the number of ␤-actin transcripts per cell (32).…”
Section: Quantitative Rt-pcr (Qrt-pcr) Microarrays and Cytokine Elisasmentioning
confidence: 99%
See 3 more Smart Citations